Reinterpretation of the substrate specificity of the voltage-sensing phosphatase during dimerization - Kruse, Martin; Kohout, Susy C; Hille, Bertil (The Journal of general physiology, 2019)
Voltage-sensing phosphatases (VSPs) cleave both 3- and 5-phosphates from inositol phospholipids in response to membrane depolarization. When low concentrations of VSP are expressed in oocytes, the 5-phosphatase reaction can be observed during large membrane depolarizations. When higher concentrations are expressed, the 5-phosphatase activity is observed with smaller depolarizations, and the 3-phosphatase activity is revealed with strong depolarization. Here we ask whether this apparent induction of 3-phosphatase activity is attributable to the dimerization that has been reported when VSP is expressed at higher concentrations. Using a simple kinetic model, we show that these enzymatic phenomena can be understood as an emergent property of a voltage-dependent enzyme with invariant substrate selectivity operating in the context of endogenous lipid-metabolizing enzymes present in oocytes. Thus, a switch of substrate specificity with dimerization need not be invoked to explain the appearance of 3-phosphatase activity at high VSP concentrations.